A Review of Recent Changes in Major Marine-Terminating Outlet Glaciers in Northern Greenland - Hill, Emily A.; Carr, J. Rachel; Stokes, Chris R. (Frontiers in Earth Science, 2017)
Over the past two decades, mass loss from the Greenland Ice Sheet (GrIS) has accelerated and contributed to global sea level rise. This has been partly attributed to dynamic changes in marine terminating outlet glaciers. Outlet glaciers at the northern margin of the ice sheet drain 40% of its area but are comparatively less well studied than elsewhere on the ice sheet (e.g. central-west or south-east). In order to improve our understanding of this region of the GrIS, this paper synthesizes previously-published research on 21 major marine terminating outlet glaciers. Over the last 130 years, there has been a clear pattern of glacier retreat, particularly over the last two decades. This was accompanied by velocity increases on the majority of glaciers for which records exist. Despite a distinct signal of retreat, however, there is clear variability within the region, which has complicated efforts to determine the precise drivers of recent changes, such as changes in ice tongue buttressing, atmospheric and /or oceanic warming, in addition to the possibility of glacier surging. Thus, there is an important need for further work to ascertain the precise drivers of glacier change, which is likely to require datasets on recent changes in the ocean-climate system (particularly sub-surface ocean temperatures) and numerical modelling of glacier sensitivity to these various forcings. Objective identification of surge-type glaciers is also required. Given that Northern Greenland is predicted to undergo greater warming due to Arctic Amplification during the 21st century, we conclude that the region has the potential to become an increasingly important source of mass loss.